2018
DOI: 10.1016/j.cviu.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Superpixels: An evaluation of the state-of-the-art

Abstract: Superpixels group perceptually similar pixels to create visually meaningful entities while heavily reducing the number of primitives for subsequent processing steps. As of these properties, superpixel algorithms have received much attention since their naming in 2003 [1]. By today, publicly available superpixel algorithms have turned into standard tools in low-level vision. As such, and due to their quick adoption in a wide range of applications, appropriate benchmarks are crucial for algorithm selection and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
322
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 457 publications
(360 citation statements)
references
References 80 publications
0
322
0
8
Order By: Relevance
“…To avoid the heavy computational cost, this paper constructs the lifted graph based on the super-pixel algorithm. As suggested by Stutz et al [15] and Wang et al [16], the super-pixel algorithms over-segments the image meshes into much smaller graphs, which greatly reduces the complexity of the following segmentation procedure. As images captured from DCT are always of high resolution, super-pixel algorithms improves the feasibility of the multicut problem.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid the heavy computational cost, this paper constructs the lifted graph based on the super-pixel algorithm. As suggested by Stutz et al [15] and Wang et al [16], the super-pixel algorithms over-segments the image meshes into much smaller graphs, which greatly reduces the complexity of the following segmentation procedure. As images captured from DCT are always of high resolution, super-pixel algorithms improves the feasibility of the multicut problem.…”
Section: Methodsmentioning
confidence: 99%
“…Superpixels can be understood as a form of image segmentation, that oversegment the image in a short computing time. Comparisons to similar approaches that can be found in (Achanta et al, 2012;Csillik, 2016;Neubert and Protzel, 2012;Schick et al, 2012;Stutz, 2015;Stutz et al, 2017) have demonstrated their advantages: The outlines of superpixels have shown to adhere well to natural image boundaries, as most structures in the image are conserved (Neubert and Protzel, 2012;Ren and Malik, 2003). Furthermore, they allow to reduce the susceptibility to noise and outliers as well as to capture redundancy in images.…”
Section: Introductionmentioning
confidence: 95%
“…State-of-the-art superpixel approaches have been compared in (Achanta et al, 2012;Csillik, 2016;Neubert and Protzel, 2012;Schick et al, 2012;Stutz, 2015;Stutz et al, 2017) considering speed, memory efficiency, compactness of outlines, their ability to adhere to image boundaries and their impact on segmentation performance. Boundary adherence is often measured via boundary recall, indicating how many true edges are missed, and via undersegmentation, indicating to what extent superpixels exceed outlines of the reference data (Achanta et al, 2012;Neubert and Protzel, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Before the surge of deep learning approaches, several algorithms based on superpixel segmentation techniques (Stutz, Hermans, & Leibe, ) were used for this task. These approaches cluster image pixels into several groups of similar and connected pixels (i.e., superpixels).…”
Section: Related Workmentioning
confidence: 99%